This is a story - Schu, John, 1981- (Candlewick Press, 2023)
"Children's literacy advocate John Schu and Caldecott Honor recipient Lauren Castillo celebrate the power of finding the perfect book--in a story that's more relevant than ever. With a sea-horse kite in hand, a child heads out with Dad to the library. On the way they stop at a park, joining lots of people, some of whom are flying kites, too. At the library, a person toting a big pile of books hands over a story on a favorite subject: the sea horse. All around, there are readers poring over books, each with their own questions, ideas to explore, hopes for the future, and imaginations ready to spark. With a warm, lyrical text and tenderly expressive illustrations, John Schu and Lauren Castillo invite us to imagine the myriad ways that books can foster connection and understanding -- and how they can empower children, through their own passions, to transform the world."--